(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article examines the role of physical education classes in shaping a healthy lifestyle among students, the importance of physical education in increasing the functional stability of the body, strengthening the cardiovascular and respiratory systems, increasing the level of general fitness, and ensuring psychological well-being, regular physical activity reduces stress levels in students, increases emotional stability, strengthens self-confidence, and develops volitional qualities.